Mapeamento da situação educacional dos alunos surdos de munícipios brasileiros atendidos pelo curso de língua brasileira de sinais na modalidade à distância - Milanez, Simone Ghedini Costa [UNESP]; Poker, Rosimar Bortolini [UNESP] (My University, 2010)
Recent years have seen a movement toward school inclusion of children with special educational needs. In Brazil, there is the formulation of laws guaranteeing rights for disabled people, giving you free access to regular classroom complemented by specialized educational services. In the case of students with deafness, the Federal Decree No. 5626 of 2005, recommends that schools offer the Brazilian sign language as language support, and should take into classrooms, an interpreter. In this study we conducted a mapping of the educational situation of students with hearing loss of 35 municipalities. There was a mode of education in which deaf students are enrolled, and also the municipalities have organized the specialized educational services for such students. Data were collected through interviews with managers of 35 municipalities. The results showed that the vast majority of municipalities participating in the study opted for the enrollment of deaf students in regular class. Only a few municipalities managers reported the existence of classes and enrollment in special schools or even the existence of deaf students out of schools. It also found that all municipalities have organized the specialized educational services, like additional offering in the resource rooms. We conclude that despite the existing difficulties, the Brazilian municipalities are gradually adjusting to the prospect of inclusive education. Continuing education courses should be offered in order to prepare more teachers to work with diversity.

Nos últimos anos assistimos um movimento voltado para a inclusão escolar das crianças com necessidades educacionais especiais. No Brasil, constata-se a formulação de leis que garantem direitos à pessoa com deficiência, proporcionando-lhe o livre acesso à sala de aula regular complementado pelo Atendimento Educacional Especializado. No caso dos alunos com surdez, o Decreto Federal nº 5.626 de 2005, recomenda que as escolas ofereçam a Língua Brasileira de Sinais como suporte lingüístico, devendo ter nas salas de aula, um intérprete. Diante disso, o presente estudo pretendeu fazer um mapeamento da situação educacional dos alunos com surdez de 35 municípios brasileiros espalhados pelo país. Verificou-se a modalidade de ensino na qual os alunos surdos estão matriculados e, também, se os municípios já organizaram o Atendimento Educacional Especializado para tais alunos. Os dados foram coletados por meio de entrevista realizada com os gestores desses 35 municípios. Os resultados demonstraram que a grande maioria dos municípios participantes do estudo optou pela matrícula do aluno surdo na classe comum. Só em poucos municípios os gestores referiram existência de matrículas em classes e escolas especiais ou mesmo a existência de alunos surdos fora das escolas. Também se constatou que todos os municípios que participaram da pesquisa já organizaram o Atendimento Educacional Especializado, do tipo complementar, oferecendo-o em salas de recursos. Conclui-se que apesar das dificuldades existentes, os municípios brasileiros estão gradativamente, se adequando à perspectiva de educação inclusiva. Neste sentido, na atual conjuntura educacional inclusiva, cursos de formação continuada devem ser oferecidos pelos sistemas de ensino de forma a preparar cada vez mais e melhor os professores.
Mapping the educational situation of the Brazilian municipalities deaf students attended the course of Brazilian language signs in distance mode
Keywords: educação; surdez; LIBRAS